Effects of pump recycling technique on stimulated Brillouin scattering threshold: a theoretical model - Al-Asadi, Hamid Ali Abed; Al-Mansoori, Mohammed Hayder; Ajiya, Mohammed; Hitam, Salasiah; Saripan, M. Iqbal; Mahdi, Mohd Adzir (Optical Society of America, 2010)
We develop a theoretical model that can be used to predict stimulated Brillouin scattering (SBS) threshold in optical fibers that arises through the effect of Brillouin pump recycling technique. Obtained simulation results from our model are in close agreement with our experimental results. The developed model utilizes single mode optical fiber of different lengths as the Brillouin gain media. For 5-km long single mode fiber, the calculated threshold power for SBS is about 16 mW for conventional technique. This value is reduced to about 8 mW when the residual Brillouin pump is recycled at the end of the fiber. The decrement of SBS threshold is due to longer interaction lengths between Brillouin pump and Stokes wave.